2016
DOI: 10.1111/bjh.13933
|View full text |Cite
|
Sign up to set email alerts
|

The Dohner fluorescence in situ hybridization prognostic classification of chronic lymphocytic leukaemia (CLL): the CLL Research Consortium experience

Abstract: SummaryThis study revisited the Dohner prognostic hierarchy in a cohort of 1585 well-documented patients with chronic lymphocytic leukaemia. The duration of both time to first treatment (TTFT) and overall survival (OS) were significantly longer than observed previously, and this is at least partly due to improved therapeutic options. Deletion 13q remains the most favourable prognostic group with median TTFT and OS from fluorescence in situ hybridization (FISH) testing of 72 months and >12 years, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 31 publications
2
45
3
2
Order By: Relevance
“…Previous authors have demonstrated that a high proportion of cells bearing tris12 is associated with a worse outcome. 3,13 In the series herein, we could not confirm this feature, neither with tris12 evaluated as a continuous variable, nor as a dichotomous variable applying the cut-off point at 60% of tris12-bearing nuclei, as previously suggested.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…Previous authors have demonstrated that a high proportion of cells bearing tris12 is associated with a worse outcome. 3,13 In the series herein, we could not confirm this feature, neither with tris12 evaluated as a continuous variable, nor as a dichotomous variable applying the cut-off point at 60% of tris12-bearing nuclei, as previously suggested.…”
contrasting
confidence: 65%
“…3 Other reports suggest a certain degree of clinical heterogeneity, with a higher incidence of second malignant neoplasms 4 and Richter transformation. 4 although the real impact of these CLL negative prognosticators in the tris12 setting remain to be fully elucidated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These aberrations are associated with distinct clinical outcome [1, 2]. In particular, del(17p) cases have the worst clinical outcome and the shortest overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%